2022
DOI: 10.3389/fpubh.2022.993700
|View full text |Cite
|
Sign up to set email alerts
|

Can a chatbot enhance hazard awareness in the construction industry?

Abstract: Safety training enhances hazard awareness in the construction industry. Its effectiveness is a component of occupational safety and health. While face-to-face safety training has dominated in the past, the frequent lockdowns during COVID-19 have led us to rethink new solutions. A chatbot is messaging software that allows people to interact, obtain answers, and handle sales and inquiries through a computer algorithm. While chatbots have been used for language education, no study has investigated their usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…In explaining the models, the analysis of variance is adopted as a special regression analysis of the dependent and independent variables. Analysis of variance is basically used for ascertaining the difference in means of samples (Asamaoh & Offei-Nyako, 2013) and relationships in modelling (Zhu et al, 2022). For the time series data obtained for this study, the analysis of variance (ANOVA) and analysis of covariance (ANCOVA) was used for the regression estimations.…”
Section: 30 Econometric Methodsmentioning
confidence: 99%
“…In explaining the models, the analysis of variance is adopted as a special regression analysis of the dependent and independent variables. Analysis of variance is basically used for ascertaining the difference in means of samples (Asamaoh & Offei-Nyako, 2013) and relationships in modelling (Zhu et al, 2022). For the time series data obtained for this study, the analysis of variance (ANOVA) and analysis of covariance (ANCOVA) was used for the regression estimations.…”
Section: 30 Econometric Methodsmentioning
confidence: 99%
“… [ 80 , 111 ] ML Can a chatbot enhance hazard awareness in the construction industry? 2022 Hazard awareness enhancement by chatbot training [ 79 ] AI Big Data Technology in Construction Safety Management: Application Status, Trend and Challenge 2022 Construction safety management [ 112 ] AI Integration of Building Information Modeling and Artificial Intelligence Systems to Create a Digital Twin of the Construction Site 2022 Hazard identification and risk management [ 113 ] …”
Section: Applications Of Ai and ML In Construction Project Lifecycle ...mentioning
confidence: 99%
“…In another study by Ref. [ 79 ], Telegram chatbot safety training and task complexity on hazard awareness were investigated. Results indicated that Telegram chatbot training positively influenced hazard awareness, particularly for participants with limited onsite experience and in less complex scenarios.…”
Section: Applications Of Ai and ML In Construction Project Lifecycle ...mentioning
confidence: 99%
“…Such complications are affected by numerous factors, including risk-taking behavior attitude, risk perception, unsafe construction equipment, geological exploration design, technical management, safety management, and construction site conditions (30)(31)(32). In this regard, many studies have suggested that chatbots and virtual training platforms can enhance the training effect (4,33). The new technology promotes the updating and upgrading training content, and ST based on virtual reality plays an increasingly important role.…”
Section: Safety Training For Construction Workersmentioning
confidence: 99%